Extension of hydrodynamic chromatography to DNA fragment sizing and quantitation. Issue 9 (September 2021) - Wang, Yanan; Zhou, Yingyan; Zhang, Dongtang; Wang, Xiayan; Liu, Shaorong
Abstract: Hydrodynamic chromatography (HDC) is a technique originally developed for separating particles. We have recently extended it to DNA fragment sizing and quantitation. In this review, we focus on this extension. After we briefly introduce the history of HDC, we present the evolution of open tubular HDC for DNA fragment sizing. We cover both the theoretical aspect and the experimental implementation of this technique. We describe various approaches to execute the separation, discuss its representative applications and provide a future perspective of this technique in the conclusion section of this review. Abstract : Hydrodynamic chromatography; Open tubular column; DNA fragment sizing; DNA fragment quantitation; Free solution separation.